All Roads Lead to Strasbourg?: Application of the Margin of Appreciation Doctrine by the European Court of Human Rights and the UN Human Rights Committee. (31st July 2017) - Shany, Yuval
ABSTRACT: The present article seeks to explore the possibility that a gap exists between the perceived rejection of the margin of appreciation (MoA) doctrine by the UN Human Rights Committee (HRC), and its actual practice of employing substitute, MoA-like approaches. The existence of such a gap might be explained by the proposition that some aspects of the MoA doctrine are an indispensable element of international adjudication involving state conduct. It may also suggest that there are policy considerations which lead some international human rights bodies not to embrace explicitly the MoA doctrine or to downplay in their jurisprudence the prominence of similar deference-granting doctrines. Section 2 of the article surveys the application of the MoA doctrine in the case law of the European Court of Human Rights (ECtHR), identifying three analytically separate prongs—application of law to facts, balancing of norms in the course of law-application and balancing of norms in the course of law interpretation. Section 3 then moves to discuss analogous legal moves taken by the HRC, while noting the remaining differences between the approaches of the two bodies. Section 4 concludes.